2012
DOI: 10.1186/1746-4358-7-1
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding practices in Bhaktapur, Nepal: a cross-sectional, health facility based survey

Abstract: BackgroundPromotion of proper breastfeeding practices for the first six months of life is the most cost-effective intervention for reducing childhood morbidity and mortality. However, the adherence to breastfeeding recommendations in many developing countries is not satisfactory. The aims of the study were to determine breastfeeding and infant feeding patterns at nine months of age and to assess factors influencing exclusive breastfeeding practices.MethodsIn Bhaktapur, Nepal, we carried out a cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
113
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(140 citation statements)
references
References 16 publications
24
113
2
1
Order By: Relevance
“…16,19,28 Ulak M et al also reported that 79% infants were introduced to complementary food before six months of age and the main reason was assumed insufficient breast milk production. 29 Holambe VM et al observed in their study that late introduction of complementary food was associated with maternal age, education and parity. 30 Limitations of our study: due to limited time and resource the study could not analyse thoroughly all the factors associated with breast feeding and complementary feeding.…”
Section: Discussionmentioning
confidence: 99%
“…16,19,28 Ulak M et al also reported that 79% infants were introduced to complementary food before six months of age and the main reason was assumed insufficient breast milk production. 29 Holambe VM et al observed in their study that late introduction of complementary food was associated with maternal age, education and parity. 30 Limitations of our study: due to limited time and resource the study could not analyse thoroughly all the factors associated with breast feeding and complementary feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Appreciate and initiate Counseling methods to reinforce specific, priority messages by health facility staff and community-based workers at all contact points with pregnant women. It also provides base line information for further study [45][46][47][48]. The study about colostrums was not conducted in bench Maji zone southern Ethiopia.…”
Section: Significance Of Studymentioning
confidence: 99%
“…15 Another study showed that 91 % mothers had fed colostrums to their babies. 6 Colostrums feeding was popular among the mothers. No other in-depth reasons were asked to the mothers who did not fed colostrums.…”
Section: Resultsmentioning
confidence: 99%
“…5 The prevalence of exclusively breastfeeding at 1, 3 and 6 months were 74%, 24% and 9%, and partial feeding was initiated in 15%, 38% and 79% babies, respectively in Bhaktapur district of Nepal. 6 The cultural food taboos and beliefs which are deeply rooted in some communities are found to influence…”
Section: Introductionmentioning
confidence: 99%